Intelligent control of a collaborative robot - Elgun Jabrayilzade (ХНУРЕ, 2026)
The paper considers an approach to intelligent control of a collaborative robot in complex and dynamic environments. A control system architecture is proposed that combines sensor fusion, adaptive control algorithms, and operator involvement in the decision-making loop. It is shown that the combination of autonomy and human-centered control increases the safety and stability of the robot’s operation under uncertainty. The presented results of numerical simulations confirm the effectiveness of the proposed approach
Keywords: collaborative robot; intelligent control; adaptive systems; sensor fusion